Effectiveness of plant essential oils derived from Curcuma longa, Illicium verum, Ocimum tenuiflorum, and Foeniculum vulgare for controlling common cutworm (Spodoptera litura) - H Passara; J Pumnuan; K Thipmanee (My University, 2021)
Abstract Four essential oils of Curcuma longa, Illicium verum, Ocimum tenuiflorum and Foeniculum vulgare were selected for insecticidal activity against the tobacco cutworm, Spodoptera litura (Fabricius) (Lepidoptera, Noctuidae) by using leaf dipping bioassay. Toxicity on second instar larvae was assessed after 24 hours of exposure. The result revealed that all the four essential oils effectively killed the larvae and showed high antifeedant activity. The highest killing amount for controlling the larvae and highest anti-feedant effect were observed in the essential oils of Curcuma longa and Illicium verum 0.75% concentration causing 100% mortality after 24 hours. These oils also presented the highest anti-feedant effect for controlling the larvae at 0.25% concentration. It seems that, plant essential oils derived from Curcuma longa and Illicium verum have an ability to be used as herbicide for controlling Spodoptera litura.
Keywords: Spodoptera litura; Foeniculum; Insect Pest Control Strategies